Changing Conceptions of "Anjing - Dogs" in Contemporary Social Contexts - Siregar, Iskandarsyah; Purnama, Ade Riyan; Gual, Anatolie (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
The presence of Generation Z (Gen Z) marks a major change in society, because they are the first group to be born and raised in the digital era. Although often referred to as "digital natives" are supposed to be highly proficient in digital technology, their level of digital literacy is still a topic of debate. This generation has been widely exposed to the internet and portable digital devices, which has shaped their worldview and communication patterns. Gen Z's reliance on electronic technology has resulted in a decline in traditional activities such as reading books, which impacts a number of cognitive and socioeconomic factors including vocabulary development, attention span, academic performance, and future economic productivity. This behavioral shift not only changes Gen Z's lifestyle, but also impacts language use and the evolution of semantics. For example, the word 'dog', which previously referred to a four-legged mammal often used as a pet or guard, has experienced a shift in meaning in the Gen Z lexicon. Now, 'dog' is often used as an additional suffix in various sentences in their communications. This linguistic phenomenon reflects a broader trend of semantic decay, in which words acquire new connotations or functions in contemporary discourse. Understanding the implications of this linguistic evolution is critical for educators, policy makers, and linguists. This report highlights the importance of adapting educational and communicative strategies to meet the needs of a generation growing up digitally influenced. By studying the complex interactions between technology, language, and social norms, we can gain valuable insights into the dynamics shaping the linguistic landscape of the 21st century.